Islam Nusantara Sebagai Wadah Agama dan Budaya - Milki Sani Yantie (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the role of Islam Nusantara as a unifier between religion and culture in Indonesia, because it is undeniable that Indonesia holds as a vast cultural superpower. This research uses a qualitative reference approach method, namely in the form of printed and electronic publications. References consist of narrative types, reportage as well as other types of types. The results and discussions in this study show that Islam nusantara can be a solution to neutralize the religion that is newly attached to the archipelago. This research concludes that the birth of Islam as a new religion in Indonesia but because of its spread using various cultures that have been inherent in Indonesia, it has become a religion that can dominate other religions. Islam Nusantara is applied in Indonesia. According to Cak Nur, Given the customs and customs of Qaidah ushul Fiqih is the source of law in Islam. Therefore, it is natural for Indonesia to apply Nusantara Islam as long as its customs and customs do not conflict with Islam.